Digital sculpting for historical representation: Neville tomb case study. Issue 2 (3rd April 2017) - Frank, Fitzpatrick; Unver, Ertu; Benincasa-Sharman, Caterina
ABSTRACT: Despite digital 3-D polygon modelling applications providing a common and powerful tool-set for archaeological, architectural and historical visualisation over recent years, the relatively recent developments in high-resolution sculpting software allow for the possibility to create digital outcomes with a degree of surface fidelity not previously obtainable from the more widely used poly-modelling software packages. Such digital sculpting applications are more commonly applied within the video games and TV/motion picture industries, the intention of this paper is to show how such tools and methodologies together with existing scanned data and some historical knowledge can remediate and re-imagine lost sculptural form. The intended research will focus on an examination and partial re-construction of the tomb of Sir John Neville, 3rd Baron Raby located at Durham Cathedral, County Durham UK.